The Application of Linear Programming into Production Schedule at Electrical Panel Company - Junaiddin, Arsyad; Syaifuddin, Dedy Takdir; Montundu, Yusuf; Zaid, Sudirman (International Journal of Membrane Science and Technology, 2023)
This study aims to implement linear programming to produce an optimal production schedule to obtain the maximum profit for an electrical manufacturing company and deliver finished products to customers on time. Linear programming was applied as a tool to carry out optimal production planning [11] every month in a business calendar year, with the objective function of maximizing Profit [12], considering the limitations of existing resources within the company. The results showed that the proposed model’s production schedule surpassed the company’s target. Despite the target being eight panels per day or 1880 panels per year for 235 working days, the model delivers 2032 panels throughout the year, or 152 panels more significantly than the target set. Manufacturers produced twelve types of parent products. However, this study presented only five types of products as decision variables in the linear programming formulations. Due to time constraints and data readiness, it is hoped that the entire parent product type can be presented as a decision variable on the next occasion. This production planning model can be one of the solutions to support the Operational Management manager in solving the problems that usually occur in manufacturing, as well as a reference for the master production schedule for procuring material needs. This study contributes to planning electrical panel production scheduling to provide optimal planning and increase the knowledge base in operation.